Impact of fruit texture on the release and perception of aroma compounds during in vivo consumption using fresh and processed mango fruits. (15th January 2018) - Bonneau, Adeline; Boulanger, Renaud; Lebrun, Marc; Maraval, Isabelle; Valette, Jérémy; Guichard, Élisabeth; Gunata, Ziya
Highlights: Impact of fruit texture on the in vivo aroma release was determined by RATD-GC/MS. Fruit texture had a significant effect on the in vivo release and perception of VOCs. The intact mango samples released more VOCs in vivo than the disintegrated samples. Abstract: Two fresh (fresh cubic pieces, fresh puree) and two dried (dried cubic pieces, dried powder) products were prepared from a homogenous mango fruit batch to obtain four samples differing in texture. The aromatic profiles were determined by SAFE extraction technique and GC–MS analysis. VOCs released during consumption were trapped by a retronasal aroma-trapping device (RATD) and analysed by GC–MS. Twenty-one terpenes and one ester were identified from the exhaled nose-space. They were amongst the major mango volatile compounds, 10 of which were already reported as being potential key flavour compounds in mango. The in vivo release of aroma compounds was affected by the matrix texture. The intact samples (fresh and dried cubic pieces) released significantly more aroma compounds than disintegrated samples (fresh puree, dried powder). The sensory descriptive analysis findings were in close agreement with the in vivo aroma release data regarding fresh products, in contrast to the dried products.